Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - FARIA, T.; Vaz, M.; Schwanz, P.; PolIe, A. (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature